Pemanfaatan Magic Straws untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa pada Materi Dimensi Tiga - Apriatni, Sri; Khaeroni, Khaeroni (PTK: Jurnal Tindakan Kelas, 2025)
The three-dimensional geometry topic in mathematics is inherently abstract, requiring students’ imagination and active engagement in conceptually constructing spatial structures. However, the instructional strategies implemented by teachers have not yet resulted in optimal student participation. To describe the effectiveness of using Magic Straws in enhancing students’ engagement and learning outcomes in Three-Dimensional Geometry. Employ the Classroom Action Research method, following the Kemmis and McTaggart model, with 34 students as subjects. Data were analyzed qualitatively and quantitatively through a reflection phase in each cycle. The success criteria were determined based on a minimum 10% increase in learning activity, an average test score of at least 75, and a minimum classical learning mastery rate of 85%. Using Magic Straws significantly enhances students’ active participation in learning. The percentage of student activity increased by 14% from Cycle I to Cycle II. The average learning outcome improved from 52.06 in Cycle I to 86.26 in Cycle II, while the classical learning mastery rate increased from 20.59% to 85.29%.  Magic Straws have proven effective in improving student engagement and learning outcomes in Three-Dimensional Geometry. Therefore, further creativity and innovation are needed in designing mathematics learning strategies to enhance students’ understanding of abstract concepts.